2015
DOI: 10.1002/chem.201502133
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Bromination of Unfunctionalized Olefins with H2O as a Nucleophile

Abstract: The dimeric cinchona alkaloid (DHQD)2 PHAL is used to catalyze an effective asymmetric bromohydroxylation of unfunctionalized olefins with H2 O as nucleophile an N-bromobenzamide as a bromine source. A variety of optically active bromohydrins are formed with up to 88 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In order to eliminate the formation of a C s -dimer during the oxidative coupling and achieve asymmetric synthesis of gonytolide A, access to enantiopure monomer 3 was required. 4c Based on reported examples of asymmetric halogenation of alkenes and phenols, 16,17 we evaluated cinchona alkaloid catalysts 29 for asymmetric bromination of (±)- 3 . After considerable experimentation, we found that the dimeric catalyst (DHQD) 2 Pyr could achieve bromination of (±)-gonytolide C to effect kinetic resolution (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to eliminate the formation of a C s -dimer during the oxidative coupling and achieve asymmetric synthesis of gonytolide A, access to enantiopure monomer 3 was required. 4c Based on reported examples of asymmetric halogenation of alkenes and phenols, 16,17 we evaluated cinchona alkaloid catalysts 29 for asymmetric bromination of (±)- 3 . After considerable experimentation, we found that the dimeric catalyst (DHQD) 2 Pyr could achieve bromination of (±)-gonytolide C to effect kinetic resolution (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in reported examples of asymmetric fluorination with cinchona alkaloid catalysts, N -fluorinated-cinchona derivatives have been characterized and identified as catalytic species. 30 We reasoned that NBS should first brominate the tertiary nitrogen 29b of the cinchona catalyst and that the resulting N -Br species may have a preference to recognize substrate enantiomers and deliver bromine to the ortho -position of 3 . Accordingly, we conducted DFT calculations of the complex of [(DHQD) 2 PyrBr] + and both enantiomers of 3 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…From the results, it is considered that the reactions of natural rubber with a bromine atom and H 2 O occur in latex stage. For instance, first, the bromine cation of NBS may attack the double bond of natural rubber to form a bromonium ion (Figure ) . Second, the resulting bromonium ion may react with H 2 O to form a bromohydrin group.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there are many reports of clean transformations in water medium [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], such as coupling reactions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], cyclizations [ 31 , 32 , 33 , 34 ], Michael additions [ 35 , 36 , 37 , 38 , 39 ], and condensations [ 40 , 41 ]. Additionally, H 2 O also participates in organic reactions as a nucleophile [ 42 , 43 ] to provide various kinds of functional compounds such as imidazo[1,2- a ]pyridines [ 44 ], amino acid salts [ 45 ], α-amino ketones [ 46 ], and 1,3-oxazinan-2-ones [ 47 ]. Thus, the studies of organic reactions in aqueous solvents or H 2 O-participating reactions are attractive in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%